Post-exposure prophylaxis for Blood-Borne Viral (BBV) Infections - Victor N. Chilaka (16936929) (2020)
Viral infections, such as human immunodeficiency virus (HIV), hepatitis B (HBV) and hepatitis C (HCV), are transmitted either sexually or through blood-borne contamination. The later causes enormous concern within health establishments and health care-workers.Post-exposure management of HIV rests on the use of triple Anti-Retroviral Therapy (ART), but special care must be taken to choose the right combination for particular circumstances, especially when the subject is pregnant or likely to get pregnant from the event.New-borns of mothers living with HIV require special attention, as maternal viral load plays a central role in their management. When viral load is not detectable, there is a good argument to avoid ART in these infants. Continued maternal ART is encouraged more so in women who intend to breastfeed.The management of exposure to Hepatitis B requires a detailed risk assessment of the source. In high-risk cases, Hep B immunoglobulin will be necessary otherwise passive immunisation with HBV vaccine will suffice.The use of anti-viral treatment for exposure to Hepatitis C remains controversial. New and potent drugs have been introduced but are quite expensive, and the cost-effectiveness of post-exposure therapy should be considered. Curative treatment now exists for HCV, and an option might be to follow exposed subjects up and give them definitive treatment if seroconversion occurs.This review discusses in details the practical steps in the management of sexual and occupational exposure to HIV and other blood-borne viruses with emphasis on preventing infections. Healthcare facilities should have tightly managed protocols for the management of exposure and the ability to start medication as early as possible when indicated. Other Information Published in: European Journal of Obstetrics & Gynecology and Reproductive Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ejogrb.2020.10.032